2012
DOI: 10.1095/biolreprod.111.096842
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Classical Bipartite/Karyopherin Nuclear Import Pathway Components in Acrosomal Trafficking and Assembly During Bovine and Murid Spermiogenesis1

Abstract: This study arose from our finding that SubH2Bv, a histone H2B variant residing in the subacrosomal compartment of mammalian spermatozoa, contains a bipartite nuclear localization signal (bNLS) but in spite of this did not enter the spermatid nucleus. Instead, it associated with proacrosomic and acrosomic vesicles, which were targeted to the nuclear surface to form the acrosome. On this basis we proposed that SubH2Bv targets proacrosomic/acrosomic vesicles from the Golgi apparatus to the nuclear envelope by uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…This apparently rapidly evolving protein variant (Figure 2) is reportedly found in the subacrosome of primates, rodents, and marsupials as well as bovids [37,49]. The use of the prefix ‘sub’ for this family seems appropriate, since residence in the subacrosome rather than the nucleus is a distinctive property that appears to be distributed throughout mammals.…”
Section: Prefixesmentioning
confidence: 99%
“…This apparently rapidly evolving protein variant (Figure 2) is reportedly found in the subacrosome of primates, rodents, and marsupials as well as bovids [37,49]. The use of the prefix ‘sub’ for this family seems appropriate, since residence in the subacrosome rather than the nucleus is a distinctive property that appears to be distributed throughout mammals.…”
Section: Prefixesmentioning
confidence: 99%
“…There are some other H2A and H2B variants, like mH2A variant, known to participate in X-chromosome inactivation, which tend to form heterotypic nucleosomes with canonical histones in vitro [39]. Furthermore, certain histone variants such as H2A.L and subH2B [51,53] were shown to be involved in the formation of protein assemblies in spermatids, which are distinct from nucleosomes, and whose exact structure is still unclear.…”
Section: Structure and Stability Of H2a And H2b Variant Nucleosomesmentioning
confidence: 99%
“…The PT of mammalian spermatozoa is compositionally subdivided into two major regions, the subacrosomal layer (SAL-PT), including the outer periacrosomal layer lying over the equatorial segment, and the postacrosomal sheath (PAS-PT) [10][11][12][13]. It was initially observed that local PAS solubilization of the PT was sufficient to elicit full oocyte activation during IVF [14].…”
Section: Introductionmentioning
confidence: 99%